Interval hypoxic training enhances athletic performance and does not adversely affect immune function in middle- and long-distance runners - Jung, W.-S.; Kim, S. W.; Park, H.-Y. (International Journal of Environmental Research and Public Health, 2020)
This study evaluated the e ects of intermittent interval training in hypoxic conditions for six weeks compared with normoxic conditions, on hemodynamic function, autonomic nervous system (ANS) function, immune function, and athletic performance in middle- and long-distance runners. Twenty athletes were divided into normoxic training (normoxic training group (NTG); n = 10; residing and training at sea level) and hypoxic training (hypoxic training group (HTG); n = 10; residing at sea level but training in 526-mmHg hypobaric hypoxia) groups. All dependent variables were measured before, and after, training. The training frequency was 90 min, 3 d per week for six weeks. Body composition showed no significant di erence between the two groups. However, the HTG showed more significantly improved athletic performance (e.g., maximal oxygen uptake). The hemodynamic function (e.g., oxygen uptake, oxygen pulse, and cardiac output) during submaximal exercise and ANS function (e.g., standard deviation and root mean square of successive di erences, high frequency, and low/high frequency) improved more in the HTG. Immune function parameters were stable within the normal range before and after training in both groups. Therefore, hypoxic training was more e ective in enhancing athletic performance, and improving hemodynamic and ANS function; further, it did not adversely a ect immune function in competitive runners. Keywords: interval hypoxic training; hemodynamic function; autonomic nervous system balance;